Penggunaan probiotik untuk meningkatkan respon imun nonspesifik ikan mas (Cyprinus carpio) - Undi, Chintia S.; Manoppo, Henky; Kreckhoff, Reni L.; Tumbol, Reiny A.; Pangkey, Henneke (Universitas Sam Ratulangi, 2020)
The aim of this research was to count the total leukocytes and phagocytosis activity of goldfish seeds treated with probiotics. The test fish used were goldfish seeds measuring 5-8 cm. 500 fish will be taken from the Tateli Fish Cultivation and Development Center (BP3I). This study used a completely randomized design (CRD) with 5 treatments, where each treatment had 3 replications. The treatments used were probiotic bacteria from the intestines of goldfish with different concentrations. The treatments tested consisted of: A: without the addition of probiotics, B: addition of probiotics 1x106 cfu / mL, C: addition of probiotics 1x107 cfu / mL, D: addition of probiotics 1x108 cfu / mL, E: addition of probiotics 1x109 cfu / mL. Each concentration of bacteria that has been prepared is then sprayed on the commercial feed evenly using a sprayer and then dried to room temperature. After drying the feed was coated with 2% egg yolk and dried again at room temperature. Fish are stocked in an aquarium measuring 60x40x40cm3 with a density of 20 fish / aquarium. Each aquarium is equipped with an aerator and a water pump for recirculation. The fish were then given feed that had been added with probiotics at the same dose and frequency of administration as in the acclimatization process. The treatment is given for 6 weeks. At the end of the treatment feeding, fish samples were taken from each experimental unit to measure immune parameters, namely total leukocytes and phagocytic activity. Based on the results of research using the probiotic Lactobacillus sp. which originated from the intestines of goldfish and added to the feed had a significant effect on increasing total leukocytes and phagocytosis activity and the optimal concenration was Â 1x107 - 1x108 cfu / mL with a duration of 6 weeks of administration